Ninja. Death touch - Bradford , Chris (Edinburgh: Barrington Stoke, 2013)
Lord Oda has sworn to destroy all ninja. Now Taka and Cho must help to protect their village from the invading samurai army, but they are outnumbered ten to one. Will they be able to save everyone? Action-packed sequel from bestselling Young Samurai author Chris Bradford. Particularly suitable for struggling, reluctant and dyslexic readers of 9+
Keywords: Adventure stories